Pengaruh Budaya Kerja Terhadap Kinerja Karyawan Pada PT Jasa Raharja (Persero) Cabang Nusa Tenggara Timur - Rahmat Laan; Hanifa Djakaria; Abdul Malik Hasyim (Jurnal Manajemen, 2019)
This study aims to analyze the influence of work culture on employeeperformance at PT Jasa Raharja, East Nusa Tenggara Branch bothsimultaneously and partially. The number of samples is 30 people,with saturated sample technique. The main instrument of datacollection is a questionnaire. Data analysis method. using multipleregression techniques. The results showed that attitudes towardswork and behavior while working together had a significant effect onemployee performance. Attitudes toward work and behavior at thetime also partially have a significant effect on performance.